Safety and efficacy of low-molecular-weight heparin in patients with acute venous thromboembolism postthrombolytic therapy as compared to unfractionated heparin: A systematic review and meta-analysis - Eman M. Mansory; Maha S. Al-Kathiry; Abdulelah Alzahrani (Iraqi Journal of Hematology)
BACKGROUND: Low-molecular-weight heparin (LMWH) is a proven treatment for patients with venous thromboembolism (VTE) with a lower risk of VTE recurrence and lower rates of major hemorrhage compared to unfractionated heparin (UFH) and have largely replaced its use in many indications, but its use around thrombolysis remains controversial. AIM: This study aims to evaluate the currently available evidence on LMWH use in postthrombolysis as compared to UFH. MATERIALS AND METHODS: Embase and MEDLINE were searched between 1992 and 2022, in addition to other sources. We included experimental and observational studies that assessed the use of LMWH as compared to UFH in patients with massive and submissive pulmonary embolism (PE) in the acute postthrombolysis phase. Data were pooled to estimate odds ratios (ORs), with 95% confidence intervals for VTE recurrence, bleeding complications and 30-day mortality. RESULTS: Three studies were included in this systematic review: one randomized controlled trial, one prospective, and one retrospective study. A total of 299 patients were treated with UFH, and 227 patients were treated with LMWH. Patients treated with LMWH had a statistically significant lower risk of major bleeding with OR 0.41 (0.17, 0.97) P = 0.04 and 30-day mortality with OR 0.44 (0.23, 0.85) P = 0.01. On the other hand, though the risk of VTE recurrence and clinically relevant non-major bleeding (CRNMB) were lower, this was not statistically significant with OR of 0.18 (0.03, 1.07) P = 0.06 for VTE recurrence, and OR of 0.75 (0.39, 1.42) P = 0.38 for CRNMB. CONCLUSION: In patients with massive and submissive PE postthrombolysis, LMWH is a reasonable option for anticoagulation with lower risk of VTE recurrence, bleeding complications and 30-day mortality when compared to UFH. However, this conclusion is largely influenced by observational data and the very limited evidence available. Certainly, more studies are needed to evaluate this clinical question.